PENGARUH KOMPETENSI PEDAGOGIK GURU TERHADAP MINAT DAN HASIL BELAJAR MATEMATIKA SISWA - Anggrainy Dana Wiharti; Mahmud; Mohammad Fikri Ramadhani Fauzi (Dar El-Falah, 2022)
This study aims to: 1) analyze the effect of teacher pedagogicalcompetence on the interest in learning Mathematics of grades V and VIof SDN Modopuro II. 2) analyze the effect of teacher pedagogicalcompetence on the learning outcomes of Mathematics students ingrades V and VI of SDN Modopuro II. This study uses a quantitativecorrelative approach. The sample in this study were students of gradesV and VI at SDN Modopuro II, totaling 40 people. Collecting datausing a questionnaire instrument, documentation, and observation.Testing the research hypothesis using simple linear regression analysis.Hypothesis testing shows that: 1) There is an influence of the teacher'spedagogical competence on the interest in learning mathematics ingrades V and VI of SDN Modopuro II, because the value of tcount ˃ttable (5.207 ˃ 2.026) and Fcount = 27.112 with a p-value of 0.000 issmaller than α = 0 .05 (0.000 ˂ 0.05). With a coefficient ofdetermination (R Square) of 0.416. The linear regression equationobtained Ŷ = (-20.513) + 1.169X. Thus Ha is accepted. 2) There is noeffect of the teacher's pedagogical competence on the mathematicslearning outcomes of students in grades V and VI of SDN Modopuro II,because the tcount < ttable (-1.164 <2.026) and Fcount = 1.354 with ap-value of 0.278 greater than α = 0.05 ( 0.278 > 0.05). With a coefficient of determination (R Square) of 0.31. The linear regressionequation obtained is Ŷ = 99.168 + (-0.463)X. Thus H0 is accepted